Advances in Nanocatalysis Research for Carbon Nanotubes Formation and Photocatalytic Degradation of Phenol - Mohamed, Abdul Rahman; Minoo, Tasbihi; Chai, Siang Piao (Universitas Diponegoro, 2007)
Catalysts daily accelerate and boost thousands of different chemical reactions, and thereby form the basis for the multibillion dollar chemical industry worldwide and indispensable environmental protective technologies. Research in nanotechnology and nanoscience is expected to have a great impact on the development of new catalysts. The detailed understanding of chemistry of nanostructures and the ability to control materials on the nanometer scale will ensure a rational and costefficient development of new and more capable catalysts for a chemical process.